2020
DOI: 10.21203/rs.2.20574/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital Health Literacy and Sport-Physical Activities: The Moderating Role of Age

Abstract: Background : The present study extends understanding of digital health literacy by exploring issues that clarify how and when sport-physical activities enhance digital health literacy measured by four types of health-related information searched on the Internet i.e., general health information, information on a specific injury or condition, specific information on a medical treatment or procedure and information regarding second opinion after visiting a doctor. Methods: We employ Tobit model on the large Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…e ultimate goal of each product or decision is to know the real outcome of the user, especially the person directly involved [27,28]. However, although the development of exercise app software has been discussed by some scholars, researchers have found that the current status of research on exercise apps for the elderly is mainly to understand how to monitor and manage the health of the elderly [29,30,32] or analyze the users' feelings toward the products [35][36][37]. ere are few studies on changes in the physical and mental health of the elderly after using exercise apps.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…e ultimate goal of each product or decision is to know the real outcome of the user, especially the person directly involved [27,28]. However, although the development of exercise app software has been discussed by some scholars, researchers have found that the current status of research on exercise apps for the elderly is mainly to understand how to monitor and manage the health of the elderly [29,30,32] or analyze the users' feelings toward the products [35][36][37]. ere are few studies on changes in the physical and mental health of the elderly after using exercise apps.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…According to statistics, in terms of the current status of COVID-19-related research, the areas of research include virus transmission and community infection [4,32], the impact of economic and social development [1,2,16], biology and sports medicine [5,6,9,49,52], epidemic prevention and decision-making [8,11,19,40], public health [10,12,15,41], psychology [17,18,41,48], and the impact on people's physical and mental health during an epidemic [10,12,14,40]. However, few studies have used the perspective of leisure exercise to explore individual physical and mental health maintenance measures [8] and future research development trends [53].…”
Section: Eoretical Framework For the Effects Of Recreational Sports Behavior On Physical And Mentalmentioning
confidence: 99%
See 3 more Smart Citations